Utilization of Fishery Waste Product: The Case of MSMEs (In Central Java, Indonesia) - Yusuf, Muhammad; Wambui Maina, Nancy; Achmad Darodjat, Tubagus (PT. Multidisciplinary Press Indonesia, 2024)
Resource management encompasses not only fishing and aquaculture activities but also the management of fishery waste, classified as animal by-products. Effective management of fishery waste, including heads, bones, scales, offal, and shells—which constitute approximately 30-40% of total fishery products—provides opportunities to mitigate pollution and boost the income of traditional coastal communities. In 2014, the FAO highlighted Indonesia’s significant fishery commodities, particularly mollusks and sea shells, which hold substantial export potential. Utilizing every part of the fish promotes environmental sustainability and creates economic benefits. This reflects a growing recognition of sustainable practices in enhancing local economies and ecological health. Indonesia's waters are divided into nine fisheries management areas (WPP). Research on Sustainability Practices in Micro, Small, and Medium Enterprises (MSMEs) indicates that MSMEs are pivotal to Indonesia’s economic development and are increasingly adopting Green Supply Chain Management (GSCM) practices to improve sustainability. In Central Java, fisheries are a key economic activity, with fish farming and processing supporting local diets and incomes. The region’s economy is diverse, with the processing industry leading, contributing 34.99% in the first quarter of 2024. Regulations for MSMEs in Central Java aim to foster growth and sustainability by providing legal protections, financial aid, and infrastructure support, enhancing the resilience and competitiveness of MSMEs, including those in fisheries. Ongoing efforts are essential to overcome implementation challenges and ensure these regulations benefit all stakeholders. This article explores the utilization of fish waste management in MSMEs.